2020
DOI: 10.1292/jvms.19-0678
|View full text |Cite
|
Sign up to set email alerts
|

Changes in ionized calcium concentration in the blood of dairy cows with peracute coliform mastitis

Abstract: We determined the clinical signs and blood ionized calcium (iCa) levels in dairy cows with peracute coliform mastitis (PCM). The clinical scores at the onset of the disease (day 0) and on day and subsequent days were significantly (P <0.01) higher than those of healthy cows. We found a positive correlation (r = 0.894, P <0.01) between iCa and total calcium (TCa) concentrations in the blood of healthy cows ; however there was no correlation from day 0 to day 3 in the blood of PCM cows. Multiple regression analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
4
3
1
Order By: Relevance
“…Three calcium homeostasis modulator genes (CALHM1, CALHM2, and CALHM3) are found in the list of positional candidate genes contributing to the GO term (Supplemental Table S3, https: / / doi .org/ 10 .3168/ jds .2020 -18209). The high ranking of these candidate genes is in line with the observation that the calcium concentration in the blood of dairy cows with and without mastitis differs, which could be an indicator for metabolic imbalance (Wegner and Stull, 1978;Hisaeda et al, 2020). No other significant overrepresentation was detected using GO.…”
Section: Markers For CM In Dsnsupporting
confidence: 74%
“…Three calcium homeostasis modulator genes (CALHM1, CALHM2, and CALHM3) are found in the list of positional candidate genes contributing to the GO term (Supplemental Table S3, https: / / doi .org/ 10 .3168/ jds .2020 -18209). The high ranking of these candidate genes is in line with the observation that the calcium concentration in the blood of dairy cows with and without mastitis differs, which could be an indicator for metabolic imbalance (Wegner and Stull, 1978;Hisaeda et al, 2020). No other significant overrepresentation was detected using GO.…”
Section: Markers For CM In Dsnsupporting
confidence: 74%
“…However, there are no published data for EDAN, neither for validation nor for diagnostic performance. In general, the mean iCa concentrations analyzed by GEM and EDAN corresponded to those reported in the literature for dairy cows at different stages of lactation (1.02‐1.20 mmol/L), especially between calving and PP3 4,8,15,38 . This finding showed that there were no large and abnormal deviations in the iCa analysis of both GEM and EDAN compared to the previously published data.…”
Section: Discussionsupporting
confidence: 84%
“…9 The present study investigated the diagnostic performance of EDAN compared to GEM based on multiple cut-off points for serum TCa and ICA. This was different from most recent studies on dairy cows, 3,4,19,38 but in line with others regarding the use of serum TCa as a reference. 19 The cut-off points of serum TCa <2.15 9,18,28 and 2.00 7,19,20,24 mmol/L for subclinical hypocalcemia were recently defined by others and used in the analysis with ROC curve for the diagnostic performance of GEM and EDAN in the present study.…”
Section: Discussioncontrasting
confidence: 63%
“…In a previous study, we observed a positive correlation between serum ionized Ca and Alb concentrations at the time of initial diagnosis in cows wit h acute mastitis [12]. The findings of the present study showed that there were positive correlations between mean serum Alb, Ca, iP, and Mg concentrations.…”
Section: Grünwaldt Et Al Reported That the Serum Globulin And Albumin...supporting
confidence: 72%